Human-Relations Training in Three Rural Manitoba High Schools: A Three-Month Follow-Up - Banman, John; Capelle, Ron (Canadian Journal of Counselling and Psychotherapy, 2012)
This study attempted to empirically test the hypothesis that the effects of human-relations training are fairly long-lasting. Human relations training groups were provided on a voluntary basis for the staffs of three rural Manitoba high schools. The participants included 8 administrators, 33 teachers, 6 counsellors, and 2 aides. A pretest-posttest (four days after group) final test (three months after group) design was used. Significant positive changes in self-actualization (as measured by the Personal Orientation Inventory), found in the posttest, were maintained in the final test. Significant positive changes in educational values (as measured by the Educational Process Opinionnaire), found in the posttest, were not maintained in the final test. Subjective evaluations, completed at the time of the final test, indicated that for most participants the group experience had been positive and there had been some lasting effect.